Constraints in garlic farming in Occidental Mindoro, Philippines, with emphasis on production challenges and market inefficiencies - MARY YOLE APPLE DECLARO-RUEDAS; EMMANUEL G. RUEDAS (Smujo International, 2025)
Abstract. Declaro-Ruedas MYA, Ruedas EG. 2025. Constraints in garlic farming in Occidental Mindoro, Philippines, with emphasis on production challenges and market inefficiencies. Asian J Agric 9: 653-662. Garlic (Allium sativum) is a high-value crop that provides important livelihood opportunities for smallholder farmers in the Philippines, yet local production remains insufficient to meet national demand, forcing the country to import over 90% of its supply, mainly from China. This study analyzed the major challenges affecting garlic farmers in Occidental Mindoro—one of the country’s key production areas in Philippines—using a descriptive-survey approach. Sixty-four respondents were purposively selected, and data were analyzed using descriptive statistics and SWOT analysis. Results showed that garlic farming remains profitable, with an average net income of PhP 185,445 per hectare and an average yield of three tons, but production is hampered by limited access to quality planting materials, climate variability, pest and disease infestations, and high input costs. Marketing inefficiencies further constrain profitability, as most farmers rely on wholesalers and middlemen, leading to low and unstable farmgate prices, while strong competition from cheap imports significantly undermines the market for native garlic. These findings underscore the need for greater institutional support, including the provision of certified seeds, affordable inputs, and targeted training in climate-resilient and pest management practices, alongside the establishment of structured marketing systems, cooperatives, and farm-to-market linkages. Addressing these gaps is critical to improving farmer livelihoods, reducing import dependence, and ensuring the long-term sustainability of garlic production in Occidental Mindoro, Philippines.